2019
DOI: 10.4103/jfmpc.jfmpc_624_19
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hydatid cyst: Review of literature

Abstract: Echinococcosis is a rare infectious disease in human being that occurs by the larval stages of taeniid cestodes of the genus Echinococcus. Human cystic echinococcosis is the most common presentation. The liver is the most common site of echinococcal cyst, followed by the lungs. The symptoms of lung infestation lead to sudden onset of chest pain, cough, fever, and hemoptysis after a cyst rupture. The diagnosis is confirmed by radiology supplemented with serology. Chest X-ray and computer tomography of chest is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
85
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 37 publications
(50 reference statements)
0
85
0
1
Order By: Relevance
“…There is a risk for hydatid cyst to recur; thus, some surgeons advocate for postoperative medical therapy to reduce the risk of recurrence. [4,5,8,18] There were no recurrences and mortality in this study; however, the follow-up period was short. Previous studies have found that recurrence rates varied between 4.6% and 22% after surgical management.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…There is a risk for hydatid cyst to recur; thus, some surgeons advocate for postoperative medical therapy to reduce the risk of recurrence. [4,5,8,18] There were no recurrences and mortality in this study; however, the follow-up period was short. Previous studies have found that recurrence rates varied between 4.6% and 22% after surgical management.…”
Section: Discussionmentioning
confidence: 59%
“…Serology is likely to be positive when multiple cysts are present, not for an isolated cyst. [5] Exposure to animals such as cats, dogs, sheep and cattle is a well-known risk factor for hydatid disease. [8] Most of the cases (94.7%) in this study were from the rural areas of KZN and EC provinces and had a history of exposure to these animals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations